2015
DOI: 10.1007/s13595-015-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thinning intensity and tree size on the growth response to annual climate in Cedrus atlantica: a linear mixed modeling approach

Abstract: Abstract& Key message With a retrospective growth analysis over 20 years, we showed that silviculture (in particular thin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…This finding is in agreement with recent results for C. atlantica stands in southern France, where the highest intensity of thinning improved post-drought recovery of growth for a period of up to ten years but not beyond (Guillemot et al, 2015).…”
Section: Thinning Benefits For Growth Following Drought Decrease Oversupporting
confidence: 93%
“…This finding is in agreement with recent results for C. atlantica stands in southern France, where the highest intensity of thinning improved post-drought recovery of growth for a period of up to ten years but not beyond (Guillemot et al, 2015).…”
Section: Thinning Benefits For Growth Following Drought Decrease Oversupporting
confidence: 93%
“…The ongoing and upcoming environmental changes and the diversification of wood uses (IPCC 2014) have deeply influenced forest management goals in the last decades; forest managers aim to define new forestry practices that combine technical efficiency, economic and environmental performance, and resistance and resilience to disturbances (D'Amato et al 2011;Doley 2010;Evans and Perschel 2009;Legay et al 2007;Lindner et al 2010;Maciver and Wheaton 2005;Parks and Bernier 2010;Seidl et al 2011). Forestry options are numerous: it is possible to shorten the rotation length so as to lower risks (Albrecht et al 2015), adapt the frequency and intensity of thinning to decrease water needs (Aldea et al 2017;Gebhardt et al 2014;Guillemot et al 2015;Martin-Benito et al 2010;Primicia et al 2013;Sohn et al 2013;Trouvé et al 2017;Van Der Maaten 2013), use other species, varieties, or improved materials, favor mixed or uneven stands supposed to be more productive (Pinto et al 2008;Pretzsch et al 2010;Pretzsch et al 2013;Vallet and Pérot 2011), and more resistant to both biotic attacks (Jactel et al 2012;Perot et al 2013) and drought (Lebourgeois et al 2013;Metz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the years 1980-1990, numerous empirical growth models were developed (Franc et al 2000;Houllier et al 1991;Porté and Bartelink 2002;Pretzsch 2009), especially in France for the main production species: European beech (Dhôte 1991), sessile oak (Le Moguédec and Dhôte 2012), Laricio pine (Meredieu 1998), Maritime pine (Lemoine 1982), black pine (Dreyfus 1993), Norway spruce (Pain and Boyer 1996), and Douglas fir (Bailly 1997). Finally, process-based growth models integrating forest management modules aimed at simulating the effect of silvicultural treatments were developed (Courbaud et al 2015;Guillemot et al 2014Guillemot et al , 2015Pretzsch et al 2008). Whatever the model type, the availability and the characteristics of databases to fit or validate the models remain fundamental, as they determine most of the domain of validity of the models (Burkhart and Tomé 2012).…”
Section: Introductionmentioning
confidence: 99%
“…plantation found that heavy thinning resulted in quicker recovery following drought [7]. Only heavy thinning (beyond current prescription levels at time of publication) reduced the impact of drought on growth for Cedrus atlantica (Manetti) in southern France [8]. Higher plantation thinning intensities also improved drought resistance, resilience and recovery for Pinus nigra and particularly Pinus sylvestris in Spain [9].…”
Section: Introductionmentioning
confidence: 99%
“…While the interaction between stand density and sensitivity to climate is highly dependent on the tree species and site under consideration, studies have shown that thinning can reduce vulnerability to changes in climate and associated disturbances [1,[6][7][8][9][10]. Both resistance and resilience to the 2003 drought was improved significantly for thinned European beech (Fagus sylvatica L.) in southwest Germany [6].…”
Section: Introductionmentioning
confidence: 99%